WHAT ARE ACCEPTED PRINCIPLES OF ACCOUNTING. - Greer, Howard C. (The Accounting Review, 1938)
Abstract The article focuses on accepted principles of accounting. A person unacquainted with accounting or the work of professional accountants, might suppose that the accepted principles of accounting are embodied in definite form somewhere in accounting literature. He might expect to find an official document-a code, or set of regulations, or series of court decisions on the subject. In any field it may be true that the broad fundamental principles are so generally known and universally accepted that their formal statement becomes unnecessary. It is accepted without argument that the ordinary financial statement of a business enterprise is presented on a going concern basis, that conservative provision should be made for probable losses, while profits are not recognized until fully realized. There are a number of vital points, however, on which no such agreement exists. There is no official declaration covering them, and they are not covered positively and uniformly in the accounting textbooks or elsewhere in the literature of the profession. Accounting practice discloses only a complete uncertainty as to what constitutes the accepted principle which should be applied.